Longitudinal study of the physical growth of schoolchildren aged 10 to 14 years: sexual dimorphism and peak growth velocity - Bergmann, Gabriel Gustavo (2008)
Monitoring physical growth during adolescence provides an important indicator of health status and also makes it possible to identify individuals’ maturity stages. The objectives of this study were to: a) describe the progression of the heights and the body mass of girls and boys from 10 to 14 years of age and the differences between the sexes, and; b) to identify the point and magnitude of peak height growth velocity (PHV) and peak body mass velocity (PMV) for boys and girls. In order to achieve these objectives 70 schoolchildren of both sexes were followed from 10 to 14 years of age. Their height (cm) and body mass (kg) were measured annually from 2001 to 2005. The results demonstrate that up until 12 years of age there are no consistent differences between the sexes, but that at 13 and 14 years of age the boys are taller and heavier than the girls. The PHV and PMV both occurred during the same periods, being from 12 to 13 for boys and from 10 to 11 for the girls. Based on these results we concluded that until the boys reach their PHV, there is no significant difference in physical growth between the sexes and that after this point the boys become taller and heavier than the girls. Furthermore, we concluded that girls reach PHV and PMV around 2 years before the boys.